Metode Perhitungan Angka Indeks Produktivitas Menggunakan Model Marvin E Mundel - Haryadi Sarjono (The Winners, 2001)
There are several measures and methods to basically perform the productivity of calculation. Marvin E Mundel (1978) methods uses calculation approach  index number, which is amount that shows the difference change of time between basic period and actual period. The result can be decrease, stabil, or increase.